Off Duty (London : Trades Union Congress General Council, 1937)
1937 1937 1930s 12 pages : illustrations These Stars are all members of their Trade Union — BRITISH EQUITY TO EVERY NURSE, I belong to a profession which has always had a rooted dislike and mistrust of organisation. Those of us that are to be any good to the Theatre are its devotees, caring for it so deeply that we are ready to work incessantly under almost any conditions because we love it. We are fortunate in this. We should all do the work we love, and love the work we do. But alas, we live in a commercial world. The Theatre is an "Industry." This very love of ours for our work can be exploited and used to drive down the conditions below the standard where decent life and work are possible. So we were forced to organise. And now as a strong, steady Trade Union we have established in London, and are establishing in the Provinces, the minimum conditions under which actors are allowed to work. Is not the nursing profession in a somewhat similar position? Nurses, like actors, are born, not made. No amount of training will really qualify a nurse if she is not inspired with a love of humanity, with a willingness to give generously of herself for the benefit of others not so healthy, not so vital, a willingness to sink personality for the sake of humanity—the larger personality. And all this can be exploited. True, Healing has not been commercialised to the extent the Theatre has. But County Councils, Municipalities, and even Hospital Committees, no less than the more commercial Nursing Homes, all feel the necessity for "economy," which so often means the overdriving of the willing horse, the use of the nurse's love of her work and devotion to duty to impose and perpetuate conditions of work and life that are unreasonable and bad. Nurses' conditions can never be luxurious (indeed the best work does not flourish so), but the patient does ask of a nurse that she shall be normal, calm, alive, and a happy human being, and all this is incompatible with a state of overstrain and discontent. Yet no real nurse wants to be a groucher or an insubordinate agitator. The solution lies, in your case as in ours, in Union Organisation, which relieves the individual from the worry of insisting on the right conditions and leaves her free to give of her best, and to go on giving more and more to the profession to which she is devoted. Sybil Thorndike [photograph] Sybil Thorndike [photograph] Laurence Olivier [photograph] Charles Laughton [photograph] Diana Wynyard [photograph] Flora Robson [photograph] Gordon Harker [photograph] Gwen Ffrangcon-Davies [photograph] Marie Burke [photograph] Godfrey Tearle Printed by the Victoria House Printing Co., Long Acre, London, W.C.2. and Published by the Trades Union Congress General Council, Transport House, Smith Square, London, S.W.1. 292/54.73/2/2